(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The curriculum of the Design-Fashion course at the Federal University of Ceara (UFC) is the object of constant reflection both by its Collegiate and by the part Structuring Teaching Nucleus (NDE), which considers the student, the professor, the institution, the market, the socio-political scenario and the country’s regulatory bodies. If thinking about the curriculum in its multiple dimensions is already a challenge in nature, the difficulties increase when this reflection is urgently required, in the face of a pandemic that affects us in all dimensions. This article aims to present the challenges and curricular possibilities of the Design - Fashion course at UFC against Covid 19. Methodologically, this is an action research that started with the bibliographic review around the categories curriculum and heigher education and was taking shape with the results obtained in field research with the teaching and student bodies. The data obtained guided the proposals for action that seemed more appropriate to the context of the pandemic.